2014
DOI: 10.3354/meps10587
|View full text |Cite
|
Sign up to set email alerts
|

Role of environmental factors on phytoplankton bloom initiation under landfast sea ice in Resolute Passage, Canada

Abstract: It has been common practice in scientific studies to assume negligible phytoplankton production when the ocean is ice-covered, due to the strong light attenuation properties of snow, sea ice, and ice algae. Recent observations of massive under-ice blooms in the Arctic challenge this concept and call for a re-evaluation of light conditions prevailing under ice during the melt period. Using hydrographic data collected under landfast ice cover in Resolute Passage, Nunavut, Canada between 9 May and 21 June 2010, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
118
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(129 citation statements)
references
References 37 publications
11
118
0
Order By: Relevance
“…We found that the biogeochemical conditions in the water column under the sea ice during late winter in the outer regions of the Canadian Arctic Archipelago were more similar to surface conditions of the offshore Arctic Ocean than what has been observed in the past in the centre of the archipelago (e.g., Mundy et al 2014). Specifically, the conditions at our ice base off Ellef Ringnes Island were similar to the low-nutrient waters of the multi-year ice-covered Canada Basin (Else et al 2013).…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…We found that the biogeochemical conditions in the water column under the sea ice during late winter in the outer regions of the Canadian Arctic Archipelago were more similar to surface conditions of the offshore Arctic Ocean than what has been observed in the past in the centre of the archipelago (e.g., Mundy et al 2014). Specifically, the conditions at our ice base off Ellef Ringnes Island were similar to the low-nutrient waters of the multi-year ice-covered Canada Basin (Else et al 2013).…”
Section: Discussionmentioning
confidence: 57%
“…Indeed, we found considerably low nutrient concentrations, as well as low C T and A T resulting in low seawater pCO 2 conditions, in the surface mixed layer throughout the study period. Furthermore, although there was a significant detectable increase in chlorophyll in the surface waters, which correlated with an increase in day length, we caution that there was no corresponding removal of nitrate'nitrite or carbon (even when normalized to salinity) and that the increase is relatively small compared to other observed ice algae and underice blooms (e.g., chlorophyll !10 mg m (2 ; Mundy et al 2014). The under-ice conditions we observed therefore suggest that there may not be sufficient nutrient levels in the northern reaches of the archipelago to instigate or sustain a large bloom as the light continues to increase.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Whether our observations in Labrador fjords can be extrapolated to other fjords along Canada's east coast is yet to be confirmed by future studies. To determine a more precise annual succession in protist community, a sampling expedition in Labrador fjords should be conducted in late spring to assess whether phytoplanktom blooms occur under the sea ice as observed elsewhere in the Arctic (see Arrigo et al 2012, Mundy et al 2014, Assmy et al 2017 and in the first half of July, immediately after the sea ice break-up. Moreover, in future investigations, it will be interesting to deter-mine how protist taxonomic composition is affected by proto-and metazooplankton grazing throughout the seasons.…”
Section: Resultsmentioning
confidence: 99%
“…In the summer, limited nutrients support a low phytoplankton biomass (Wassmann & Reigstad 2011), with episodic bloom conditions facilitated by occasional nutrient availability . These phytoplankton blooms, although responsible for the bulk of annual production, are usually restricted to open waters (but see Arrigo et al 2012;Mundy et al 2014). Boetius et al (2013) also showed that sinking ice algae aggregates constitute an important food input to benthos in the Arctic basins.…”
mentioning
confidence: 99%